Modified high dorsal procedure for performing isolated anatomic total caudate lobectomy (with video). Issue 1 (December 2016) - Ochiai, Toshiya; Ishii, Hiromichi; Toma, Atsushi; Ishimoto, Takeshi; Yamamoto, Yusuke; Morimura, Ryo; Ikoma, Hisashi; Otsuji, Eigo
Abstract Background Isolated anatomic total caudate lobectomy is indicated in patients who have liver tumors limited to the caudate lobe. However, isolated caudate lobe resection is a challenging surgical procedure that required safe and reliable techniques. All portal and hepatic veins that connect this area originate from the first branch of the portal vein or vena cava; therefore, the operator must be cautious of the potential for massive bleeding. Methods The important points regarding the safety of our procedure include creating an optimal surgical view and preparing for accidental bleeding before parenchymal dissection. Sufficient mobilization and removal of Spiegel's lobe from the left to the right side of the vena cava allows the operator to perform parenchymal dissection under a right- or front-side view. Results We have performed this technique in two patients with HCC and one patient with primary cystadenocarcinoma. The average operative time and amount of blood loss were 435 min and 1137 ml, respectively. No operative mortalities or postoperative complications were observed in any of the patients. Our three patients are currently doing well without any recurrence. Conclusion Our modified high dorsal resection procedure can be used to safely remove the entire caudate lobe.